Evaluating resource utilization efficiency in urban land construction of Yangtze river economic zone under technological progress - Wei, Wei; Qian, Xiaoyan; Lin, Qing; Zheng, Qiongjie; Cao, Yu; Chen, Xiding (Frontiers in Environmental Science, 2022)
Based on the economic models of DEA-Malmquist, this paper estimated the land utilization efficiency by considering dimensions such as energy, water and economic inputs in the Yangtze River Delta urban agglomeration from 2004 to 2016, and analyzed its spatial and temporal evolution pattern and characteristics. Then use the Tobit model to explore the main influencing factors, and examine the contribution of each influencing factor, such as technical progress. The research results show that the urban construction efficiency and the distance from the port have a “∽” curve relationship, verifying the “center-periphery” theory of new economic geography. It is also found that the effective radiation distance of the current economic center Shanghai to the surrounding area is 361.5 km. The structural analysis of the efficiency of construction land shows that the market mechanism has not played a fundamental role in the allocation of construction land resources, the improvement of the quality of labor force, and the expansion of capital clustering with industry is the main driving factor to support the efficiency of construction land use in the Yangtze River Delta region. We suggest that more efforts will be needed to reform market mechanisms and improve technological progress in the near future.